Child poverty and public policy - Chafel, Judith A. (The Urban Institute Press, 1993)
Child poverty / Judith A. Chafel -- Profiles of children and families in poverty / Judith S. Musick -- Who are the poor? A demographic perspective / William H. Scarbrough -- Children of poverty / Suzanne M. Bianchi -- Childhood poverty and child maltreatment / Joan I. Vondra -- The child in poverty / Elsie G.J. Moore -- The 101st Congress / Sandra L. Hofferth -- Human capital / Harold Watts -- Advocacy for children in poverty / Judith A. Chafel and Kevin Condit -- Conclusion: Integrating themes about child poverty in search of a solution / Judith A. Chafel.